Nitrous Oxide Consumption Potential in a Semi-Arid Agricultural System: Effects of Conservation Soil Management and Nitrogen Timing on nosZ Mediated N2O Consumption - McDonald, Mark D.; Lewis, Katie L.; DeLaune, Paul B.; Boutton, Thomas W.; Reed, Jacob D.; Gentry, Terry J. (Frontiers in Environmental Science, 2021)
Agricultural soils account for less than 10% of the total greenhouse gas (GHG) emissions in the USA but about 75% of nitrous oxide (N2O) emissions. Soil conservation practices, such as no-tillage, have the potential to mitigate GHG emissions. We examined the short-term consequences of no-tillage with a winter wheat cover crop (NTW) and no-tillage winter fallow (NT) on N2O emissions, N2O reducing bacterial populations, and overall soil bacterial abundance during the summer growing season in the southern Great Plains, USA. Conservation practices were coupled with nitrogen (N) fertilizer application timing (100% pre-plant, 100% mid-season, 40% pre-plant 60% mid-season, 100% pre-plant with N stabilizer). In addition, N2O emissions were measured to determine any functional effects of altering N fertilizer timing and changing bacterial populations. The combination of N treatment and conservation practice affected nosZ clade II abundance in the second year of the study. Diversity of nosZ clade II was evaluated to determine effects on non-typical N2O reducers which were highly abundant in this study. No nosZ clade II diversity effects were determined, although some clustering of conservation system and N treatments was observed in the second year. Nitrogen treatment affected N2O-N emissions during the summer of both years, likely related to overall increased microbial activity and N fertilizer application. Negative fluxes (consumption) of N2O-N were observed in every treatment and tillage combination and were most pronounced in the control (0 kg N ha-1). Negative fluxes are likely due to a combination of low inorganic-N concentrations at various points during the year and a robust clade II population driving N2O consumption. Altering conservation system and the timing of N fertilizer application affects the microbial community and will likely continue to select for unique communities as the system matures. This will also likely further impact N2O emissions from the system and may increase the rate and frequency of N2O consumption.